Applications of thermal processing in pharmaceutical drug product development - Salgado, Carlota de Lacerda (2013)
The process of approval for a new drug product takes several years. Challenges in modern pharmaceutical drug product development are innumerous. From early research until phase III clinical trials, new drug compounds undergo several of changes. One of the main goals is to obtain an optimal bioavailability profile, which means efficiency, along with ensuring safety standards. Presently, poor soluble molecules represent a considerable percentage of new compounds, meaning that bioavailabilty and absorption profiles are compromised. To overcome such issues, solid molecular dispersions have been recognized as a possible solution. The pharmaceutical industry, in order to improve some manufacturing techniques and tackle issues like poor solubility of molecules, has been applying thermal processes used in other industries such as food or plastics industries. Some processes, for example, hot melt extrusion and injection molding, were employed to create tablets, capsules and other drug delivery sistems with success. To understand in detail these thermal processes further investigation and research are required. Eventually, other thermal methods could also be of benefit for better and improved manufacturing processes of new drug products.